Kritik Asy-Syaukani terhadap Eksploitasi Alam dalam Tafsir Fath al-Qadīr (QS. Al-A‘raf: 56) - Ahmad Rayhan; Baiq Intan Amalia R (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This article examines al-Shawkānī’s critique of environmental exploitation through his interpretation of Qur’anic prohibitions against corruption on earth (QS. al-A‘rāf: 56) in Fath al-Qadīr. Contemporary ecological crises increasingly demand ethical and theological responses rooted in religious texts. This study aims to analyze al-Shawkānī’s exegetical reasoning, methodological approach, and ecological implications derived from the verse. Employing qualitative library research with a descriptive-analytical method, primary data are drawn from Fath al-Qadīr, while secondary data include contemporary studies on Islamic ecotheology and Qur’anic environmental ethics. The findings indicate that al-Shawkānī interprets fasād (corruption) not merely as moral or social deviation but also as actions disrupting the natural order established by God. His interpretation implicitly criticizes exploitative human behavior toward nature. The study concludes that al-Shawkānī’s tafsīr provides a normative Islamic framework for environmental ethics relevant to modern ecological challenges.